2021
DOI: 10.2147/dddt.s278002
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin Sensitizes Breast Cancer Cells to Tamoxifen by Downregulating microRNA-15b via the FOXO1/CCND1/β-Catenin Axis

Abstract: Background: Paeoniflorin (Pae) possesses anti-tumor activity in various malignancies. However, it is unclear whether Pae plays a sensitizer role in breast cancer (BC) and the molecular mechanisms involved in this process. Our oligonucleotide microarray revealed that microRNA (miR)-15b is the most significantly downregulated miRNA in MCF-7/ 4-hydroxytamoxifen (4-OHT) cells treated with Pae. This paper summarized the relevance of Pae in BC cell endocrine resistance to tamoxifen (Tam) and the molecular mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…So, we hypothesize that TRIM28 is linked to immune cell infiltration and significantly promotes tumor progression in LIHC. The hypothesis is in accordance with the results of these past studies [ 11 14 ].…”
Section: Introductionsupporting
confidence: 93%
“…So, we hypothesize that TRIM28 is linked to immune cell infiltration and significantly promotes tumor progression in LIHC. The hypothesis is in accordance with the results of these past studies [ 11 14 ].…”
Section: Introductionsupporting
confidence: 93%
“…35 The transcription factor FOXO1 binds to the CyclinD1 promoter sequence to influence gene expression. 36 Accumulating studies have reported that FOXO1 plays an important role in early placental development and is involved in early pregnancy loss. 37,38 Under oxidative stress, FOXO1-mediated trophoblast integrin β3 expression could be impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, among all women, the most frequently detected and diagnosed and the most lethal type of cancer is breast cancer (BC) (1). Distant metastasis and drug resistance represent the major causes of death in patients with BC (2)(3)(4)(5)(6). In particular, bone is one of the most frequent distant metastases in BC patients and bone metastasis arises in approximately 80% of advanced BC patients (7).…”
Section: Introductionmentioning
confidence: 99%
“…Hoxa5microrna-26a-5p promotes osteosarcoma cell proliferation and migration by targeting in vitro and in vivo ( 10 ). Previous literature suggests that, both in vitro and in vivo , paeoniflorin regulates the migration and invasion of breast cancer cells by down-regulating microrNA-15B through FOXO1/CCND1/β-catenin axis ( 6 ). Previous studies have also indicated that CEP55 was a key regulator in BC spinal metastases by Bioinformatics Analyses ( 11 ).…”
Section: Introductionmentioning
confidence: 99%